2022
DOI: 10.3762/bjoc.18.147
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis of unsymmetrical salens for the preparation of Co–salen complexes and their evaluation as catalysts for the synthesis of α-aryloxy alcohols via asymmetric phenolic kinetic resolution of terminal epoxides

Abstract: In this paper, we report the mechanochemical synthesis of unsymmetrical salens using grinding and ball milling technologies, respectively, both of which were afforded in good yield. The chelating effect of the unsymmetrical salens with zinc, copper, and cobalt was studied and the chiral Co–salen complex 2f was obtained in 98% yield. Hydrolytic kinetic resolution (HKR) of epichlorohydrin with water catalyzed by complex 2f (0.5 mol %) was explored and resulted in 98% ee, suggesting complex 2f could serve as an e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…All these studies identify the technical obstacles in our efforts to obtain the targeted complexes in high purity, despite the simplicity of the system and previous reports for one or twostep procedures. [33][34][35][36][37] Furthermore, the produced complexes are susceptible to absorbing moisture from the environment as determined by elemental analysis (ESI †); therefore, the nal complexes should be stored in the oven at 60 °C or be "activated" before use in any catalytic reaction. All these factors are essential when applying these chiral complexes in the asymmetric A 3 coupling reactions or for redox purposes.…”
Section: Complex Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies identify the technical obstacles in our efforts to obtain the targeted complexes in high purity, despite the simplicity of the system and previous reports for one or twostep procedures. [33][34][35][36][37] Furthermore, the produced complexes are susceptible to absorbing moisture from the environment as determined by elemental analysis (ESI †); therefore, the nal complexes should be stored in the oven at 60 °C or be "activated" before use in any catalytic reaction. All these factors are essential when applying these chiral complexes in the asymmetric A 3 coupling reactions or for redox purposes.…”
Section: Complex Synthesismentioning
confidence: 99%
“…Inspired by the aforementioned solventless A 3 reports and given the synthetic simplicity of these two steps, we envisioned the solventless ligand, Cu(II)-N 2 O 2 salen complex, and PAs synthesis as feasible. To the best of our knowledge, a few studies have already reported the solventless synthesis of salen based complexes in one-pot 33 or two steps, [34][35][36][37] but no report identies the synthesis of the ligand, complex and PAs mechanochemically. The results of this effort and the scope and limitations of this approach are described herein.…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, salen and salophen species constitute an important class of ligands in coordination chemistry due to their high affinity for different metal ions and their chemical versatility [89, 90] . Recently, the use of mechanochemistry for their synthesis [26, 27, 65, 91–93] in both batch and continuous multigram scales makes them a relevant example in this category. For instance, in 2014, James et al.…”
Section: Upscaling Mechanochemistrymentioning
confidence: 99%
“…The former adds to this growing body of mechanochemically prepared coordination complexes, and the latter demonstrates the feasibility of increasingly complex one-pot reaction systems via mechanochemistry, with notable prior examples from Friščić, Lamaty, James, Hanusa, Garcia, and others. 24–48…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, mechanochemical synthesis of transition and main group metal coordination complexes, [24][25][26][27][28][29][30][31][32][33][34][35] and germane to this work, Schiff base species, has gained increasing attention. [36][37][38][39][40][41][42][43][44][45][46] This work highlights the synthesis and stability of four transition metal complexes, and the application of mechanochemistry towards the dynamic assembly of a complex multi-ligand, multi-metal system. The former adds to this growing body of mechanochemically prepared coordination complexes, and the latter demonstrates the feasibility of increasingly complex one-pot reaction systems via mechanochemistry, with notable prior examples from Friščić, Lamaty, James, Hanusa, Garcia, and others.…”
Section: Introductionmentioning
confidence: 99%